Caracterización del ovino criollo en las comunidades del distrito de Lambrama (Apurímac, Perú) - Bustinza Choque, A. V. (2024)
The study was carried out with Creole sheep in flocks from the communities of Cruzpata and Siusay, both in the Lambrama district, Apurímac, Peru. The study aimed to characterize its productive capacity for meat and wool. Samples were taken from 60 sheep from two flocks to determine live weight, carcass weight, carcass yield, fleece weight and lock length. In addition, using 187 sheep from six flocks from the same area, samples of rib wool (10 g) were taken for analysis using OFDA 2000 equipment. The phenotype of the Creole sheep presents an angular body covered with fleece of various colours; bare face, belly and long legs, which grazes the puna, in an extensive system and without technical support from the State. Live weight, carcass weight and carcass yield are low, mainly affected by age, with variations like what occurs in other places in the mountains; Measurements of fleece weight and lock length are affected by age and sex, and by the lack of periodic shearing. The textile characteristics of the wool show medium fineness, with high variability, with relatively high comfort and spinning fineness indexes; better on the fleece of two-toothed females. The most important correlations were between fibre diameter (DM) and comfort factor (FH) (r=-0.5925); between DM and fineness of yarn (FH) (r=0.5857) and between FC and FH (r=-0.8767), which would indicate that the wool from the Lambrama area is of good quality for the textile industry.